Implementation Of Digital Marketing Strategies To Increase The Number Of Clients At PT. Rezeki Surya Intimakmur - Muhammad Taufikurrahman; Albari Albari (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to analyze the implementation of digital marketing strategies via Instagram by PT. Rezeki Surya Intimakmur, the research method used was in-depth interviews with three respondents who had professional backgrounds in the company. The research results show that the company has adopted various strategic steps, including market research, forming a special team, determining structured content, and adjusting the marketing timeline to optimize their presence on Instagram. These findings indicate that the digital marketing strategies implemented have increased brand visibility, engagement with audiences, and conversion of followers into potential clients, despite challenges in competition and production of quality content. The managerial implications of this research emphasize the importance of a deep understanding of target audience behavior and adaptation to digital technology to maintain a competitive advantage in the construction industry.